2015
DOI: 10.7448/ias.18.1.19305
|View full text |Cite
|
Sign up to set email alerts
|

Improved identification and enrolment into care of HIV‐exposed and ‐infected infants and children following a community health worker intervention in Lilongwe, Malawi

Abstract: BackgroundEarly identification and entry into care is critical to reducing morbidity and mortality in children with HIV. The objective of this report is to describe the impact of the Tingathe programme, which utilizes community health workers (CHWs) to improve identification and enrolment into care of HIV-exposed and -infected infants and children.MethodsThree programme phases are described. During the first phase, Mentorship Only (MO) (March 2007–February 2008) on-site clinical mentorship on paediatric HIV ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…There is an urgent need for pediatric-specific strategies for intensified case finding and improved management of HIV-infected children on ART. Given the success of community health worker-driven interventions in addressing pediatric HIV in this setting, 16,17,36 we are using this data to integrate pediatric TB case-finding and management into an existing community health worker focused intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an urgent need for pediatric-specific strategies for intensified case finding and improved management of HIV-infected children on ART. Given the success of community health worker-driven interventions in addressing pediatric HIV in this setting, 16,17,36 we are using this data to integrate pediatric TB case-finding and management into an existing community health worker focused intervention.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Hospitals and health centers vary primarily by the concentration of infrastructure and experienced personnel—hospitals often have at least one medical doctor on staff, and may have access to chest radiography, whereas health centers typically do not.…”
Section: Study Population and Methodsmentioning
confidence: 99%
“…Early community health worker engagement increases enrollment of HIV-exposed and -infected infants and young children in care (Ahmed et al, 2015) and positively influences exclusive breastfeeding and child growth (Tomlinson et al, 2014). However, this review found lay and community-based health workers’ to have unclear status and roles, which can lead to health workers performing tasks outside their training or not living up to expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The Tingathe Program in Malawi utilizes community health workers to conduct community-based HIV testing and case finding resulting in more than 2500 HIV-exposed and HIV-infected children enrolled in care from 2008 to 2011. A 10-fold increase in enrollment of HIV-infected children into care from 3.2/month preintervention to 32.7/month postintervention was observed [55,76,77]. In Tanzania, a community-based testing campaign focused on children called Know Your Child’s Status conducted 2994 tests in children with 108 new cases identified (3.6%) [78].…”
Section: Promising Strategies For Pediatric Case Findingmentioning
confidence: 99%